The Role of “Sera & Sora: Menjelajahi Dunia Remaja” E-comic in Reducing Early Marriage Intention Among Adolescents - Dewantari, Anindhea Putri Kusuma; Andayani, Tri Rejeki (Faculty of Psychology, Universitas Gadjah Mada, 2025)
Early marriage remains a serious problem in Surakarta City, with a high number of marriage dispensation applications caused by extramarital pregnancy and a lack of reproductive health education. This study examined the effect of the e-comic “Sera & Sora: Exploring the World of Teenagers” in reducing early marriage intention. This e-comic is based on the lessons of Serat Widya Pramana, which contains comprehensive sexual education based on local wisdom. This quasi-experimental study employed a control group design with dependent pre- and post-test samples. The participants were 34 adolescents aged 15–18 years in Surakarta, who were divided into experimental and control groups. Results from an independent samples t-test showed that reading the e-comic significantly reduced intention to marry early (p = 0.017; p < 0.05), with average post-test scores for the experimental group being lower (50.41) than for the control group (56.58). These results suggest that e-comics could be an effective intervention for preventing early marriage.